Impact resistance of foamed concrete slab and its modifications subjected to hemispherical impactor - Hadipramana, Josef (2015)
This research work examined the interplay between three main methods: experimental works, analytical model and numerical simulation. The three methods employed slabs of foamed concrete and its modifications. The modifications of foamed concrete included foamed concrete substituting sand with Rice Husk Ash (RHA) and foamed concrete reinforced by Polypropylene fibre (PF). Experimental work produced properties data of density, compressive strength, tensile strength, modulus of elasticity and Poisson’s ratio of slab specimens. The experiment of impact was conducted by using falling-weight impact tower method to get the depth of penetration data. The depth of crater as product of impact is called penetration depth. The basic properties of materials were used to run the numerical simulation and analytical model. The simulation applied the FE/DE method, whilst the analytical model was conducted by applying various theories and all its support from previous researchers both in empirical and non-empirical. The slab target subjected to hemispherical impactor with 7.7, 8.9 and 9.9 m/s impact velocity produced the crater without spalling or scabbing. This impact phenomenon was due to effect of porosity in matrix of foamed concrete and its modifications as foam material. Foamed concrete modifications were stronger than foamed concrete, which gave the shallower penetration depth than penetration depth of foamed concrete. Resistance of slab specimens subjected to impact loading can be predicted by its penetration depth. It can be determined by the assumption, when impactor hit the slab target, the diameter of impactor shank entirely into target due to porosity. The dimensional of penetration depth was derived when the impactor had kinetic energy and target initiate gave a reaction by its compressive strength against the force of impact. The dimensional penetration depth can be used as a formula to predict penetration depth of foamed concrete and its modification slabs subjected to hemispherical impact loading. The numerical simulation results were validated by the experimental results. Those three of analyses methods showed a tendency the same results for penetration depth.